The Influence of Internal Control, Company SOP and Auditor Professionalism on Fraud Prevention Measures - Rudy Budiatmaja; Yanuar Ramadhan (Jurnal ASET (Akuntansi Riset), 2022)
Main Purpose -  The main objective of this study is to determine the effect between variables, namely internal control, company SOPs, and auditor professionalism with simultaneous and partial fraud prevention actions that occur in bakery companies.Method - Purposive sampling in the study when it was a saturated sample of 105 employees of a bakery company listed on the Jakarta Stock Exchange for the 2017-2021 period. This research is quantitative as the method so that the data is tested with SPSS IBM 22 through multiple regression approach.Main Findings - Internal control (PI) has a positive and significant effect on fraud prevention measures because high internal control reflects lower fraud risk according to the complexity of company procedures and the complexity of the business itself. The company's SOP (SP) has a positive and significant effect on fraud prevention because the company's SOP that is carried out properly by all company employees will provide guidelines for all employees to submit and do it. Auditor professionalism (AP) has a positive and significant effect on fraud prevention measures because it can be assumed that the quality and professional competence of auditors can implement higher standards in presenting financial information in a transparent and accountable manner.Theory and Practical Implications - The current research implications are focused on future investors, companies and researchers. The implication of this research concludes that with the implementation of internal control, company SOPs as well as high professional auditors and regular audit frequency can guarantee high quality of company financial information and free from fraud.Novelty – Previous researchers only focused on the fraud triangle theory with the location of service companies as indicators for pressure, opportunity and rationalization, but in this study the researchers took Gone theory which focused on the authority of power, the demands of life needs and the prestige of the leadership lifestyle that occurred in bread company.